The Hydrogen Bike: Communicating the Production and Safety of Green Hydrogen - Glover, Katherine; Rudd, Jennifer A.; Jones, Daniel R.; Forde, Elaine; Warwick, Michael E. A.; Gannon, William J. F.; Dunnill, Charles W. (Frontiers in Communication, 2021)
As the international community aims to reduce its reliance on fossil fuels, green hydrogen has great potential to replace methane as a clean source of fuel. A novel public engagement activity, The Hydrogen Bike, has been developed to demonstrate the production and use of green hydrogen from water. The aim of the activity is to educate, entertain and inform young people and adults so that they have an opportunity to form an opinion about the use of hydrogen as a fuel. Using a novel two-part data collection system participants are briefly surveyed for their opinion on hydrogen before and after participating in The Hydrogen Bike activity. Through this we have found that most participants (73%) are considered to have no opinion or a neutral opinion on hydrogen before participating in The Hydrogen Bike activity. After participation 88% of those who were originally neutral or had no opinion on hydrogen self-reported a positive feeling about hydrogen. The method of data collection was quick, intuitive and suitable for an audience attracted from passing footfall.